THE SOCIOLOGICAL ANALYSIS OF THE FAILURE OF UJAMAA POLICY - Keskin, İbrahim; Abdalla, Mohd Juma (Bursa Teknik Üniversitesi, 2019)
The introduction of the Ujamaa[1] policy was regarded as a step forward to the socio-political and economic changes in the post-independent period in Tanzania. Nyerere as the founder of the Ujamaa policy, in his side, stood firm to ensure the Ujamaa policy restore the personal dignity and the socio-economic welfare of Tanzanians which were lost during the colonial period. The Ujamaa policy was practiced almost two decades, and thus it could have brought the intended goals but it couldn’t in the way that many Tanzanians lost their hopes especially on the means which were used to operate the Ujamaa policy. The failure of the Ujamaa policy in the restoration of human dignity and socio-economic and political welfare have been noticed to be a cornerstone for its decline as argued by many scholars. But this article explores the main reasons which necessitated to the demise of the Ujamaa policy and opened the doors for modernization.   [1] Ujamaa: is a Swahili word which refers to socialism. This was policy was applied by Nyerere in the establishment of a communal society in post-colonial Tanzania. also, the term refers to familyhood

Ujamaa[1] politikası, bağımsızlık sonrası dönemde sosyo-politik ve ekonomik değişikliklere doğru atılmış bir adım olarak kabul edilmiştir. Nyerere, kurucu olarak, kendi açısından Ujamaa politikasının sömürge döneminde kaybedilen insan onurunu geri kazanmak için politikayı restore etmek olarak tanıtmıştır. Ujamaa politikası yaklaşık yirmi yıl uygulanmasına rağmen hedeflenenleri gerçekleştirilememiştir. Söz konusu başarısızlıkla birlikte bu politikanın uygulanma biçimi birçok Tanzanyalı’nın umutlarının tüketmesine yol açtımıştır., kaybedilen insan onurunun restorasyonu ve sosyo-ekonomik ve politik refah elde etmedeki başarısızlığı, birçok bilim insanının da tartıştığı gibi, Ujamaa politikasının uygulanmasındaki başarısızlığın ana nedeni olarak görülmüştür. Bu makale, söz konusu nedenlerle birlikte, Ujamaa politikasından vazgeçmeyi gerektiren diğer nedenleri de gün yüzüne çıkarmayı ve Tanzanya'nın modernleşme sürecine nasıl girdiğini göstemeyi amaçlamaktadır. [1]  Ujamaa: Post-kolonyal dönemde Tanzanya’da  Nyrere tarafından inşa edilen sosyalist  politikayı referans için kullanılan ve Tanzanya’nın geleneksel aile yaşamını da çağrıştıran Swahilice  bir kelimedir.
THE SOCIOLOGICAL ANALYSIS OF THE FAILURE OF UJAMAA POLICY
Keywords: Sociology; Sosyoloji